The experience of reading philosophy - Whistler, Daniel (Frontiers in Psychology, 2022)
Reading is not a peripheral philosophical pastime (i.e., what we do when we tire of thinking for ourselves); it constitutes most of what we do when we do philosophy. And the experience of reading philosophy is much more than just a series of interpretative acts: the philosopher-reader is subject to, among other things, sensations, passions, emendations and transformations. In this essay, I argue that a full account of philosophical reading should outline some of the sociological structures that determine how different communities of philosophers (within and outside the academy) construct such experiences, as well as describe in detail the ways in which philosophers encounter (or fail to encounter) truths while reading. It should, that is, describe all the ways in which philosophy acts upon readers and the various effects that result.